2016
DOI: 10.1038/srep33137
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Eu(III) into Calcite under Recrystallization conditions

Abstract: The interaction of calcite with trivalent europium under recrystallization conditions was studied on the molecular level using site-selective time-resolved laser fluorescence spectroscopy (TRLFS). We conducted batch studies with a reaction time from seven days up to three years with three calcite powders, which differed in their specific surface area, recrystallization rates and impurities content. With increase of the recrystallization rate incorporation of Eu3+ occurs faster and its speciation comes to be do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…However, such a statistical average is often not suited to accurately describe local changes induced by a guest ion in the structure of a solid solution. In contrast, different species on a given crystallographic site and the deviation of the local structure from the ideal crystallographic geometry can be directly determined and characterized by TRLFS . TRLFS gives information on the geometry in the first coordination shell of the luminescent probe (Eu 3+ ), and is therefore capable of determining specific structural effects during solid solution formation, such as the local symmetry of doping sites or the number of non‐equivalent species.…”
Section: Introductionmentioning
confidence: 78%
“…However, such a statistical average is often not suited to accurately describe local changes induced by a guest ion in the structure of a solid solution. In contrast, different species on a given crystallographic site and the deviation of the local structure from the ideal crystallographic geometry can be directly determined and characterized by TRLFS . TRLFS gives information on the geometry in the first coordination shell of the luminescent probe (Eu 3+ ), and is therefore capable of determining specific structural effects during solid solution formation, such as the local symmetry of doping sites or the number of non‐equivalent species.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, the crystallochemical properties of REE 3+ are similar to those of trivalent actinides, which present at this oxidation state (i.e., +3) when the oxidation reduction potential at the geological disposal site is low, e.g., [2]. It was shown that some actinides and lantanides readily incorporate into calcite, e.g., [3,4].…”
Section: Introductionmentioning
confidence: 92%
“…Such substitution is likely valid for REE 3+ with the involvement of a charge balance mechanism. For example, the proposed incorporation mechanisms for Eu 3+ involve: (i) the formation of vacancies (Eu 2x (CO 3 ) 3 ) solid , e.g., [3]; (ii) the incorporation of OH − (EuOHCO 3 ) solid , e.g., [3]; and (iii) the incorporation of Na + with a formation of EuNa(CO 3 ) 2 [2,11]. Spectroscopic data [11,12], as well as a recent experimental study [10], suggest the incorporation of REE into calcite accompanied by the incorporation of Na + .…”
Section: Introductionmentioning
confidence: 99%
“…(64) We can, however, reject aragonite formation or recrystallization to calcite as there is (1) no trace of aragonite neither in the XRD analyses ( Figure S1) nor in the Raman spectroscopic spot analyses of the crystal interiors and (2) dominant scalenohedral habit of the crystals, which rules out pseudomorphic recrystallization after aragonite that typically consists of acicular crystals of the orthorhombic system. Trivalent Eu and other trivalent ions (e.g., Am) may be structurally incorporated and replace Ca in the calcite lattice,(65-67) but thermodynamic considerations and spectroscopic results(66, [68][69][70]show that a range of incorporation species and potential endmember phases can be involved.…”
Section: Incorporation Of Metals Into Calcitementioning
confidence: 99%